Lemmus amurensis Vinogradov 1924 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lemmus amurensis Vinogradov 1924 Lemmus amurensis Vinogradov 1924, Ann. Mag. Nat. Hist., ser. 9, 14: 186. Type Locality: Russia, Siberia, Pikan, on Zeya River, a tributary of the Amur River. Vernacular Names: Amur Brown Lemming. Synonyms: Lemmus chrysogaster J. A. Allen 1903; Lemmus flavescens Vinogradov 1925; Lemmus ognevi Vinogradov 1933; Lemmus xanthotrichus Vinogradov 1925. Distribution: Larch taiga of E Siberia; from the Arctic coast between the Lena and Kolyma Rivers southeastward onto the Kamchatka Peninsula, and southward through the Verkhoyansk and Cherskogo Mtns and the Omolon River to the upper Amur River basin and region east of Lake Baikal; also on islands in the New Siberian Arch. (Novosibirskiye Ostrova) (Chernyavskii et al., 1980, 1993; Federov, 1999 a Jarrell and Fredga, 1993:Fig. 2). Conservation: IUCN – Lower Risk (lc). Discussion: Revised by Chernyavskii et al. (1980); additional chromosomal data analyzed by Gileva et al. (1984). The distinctiveness of L. amurensis has been reaffirmed by Chernyavskii et al. (1993), who studied karyotypes, craniodental traits, and pelage coloration and reported its range extension in the Kamchatka Peninsula. Fedorov et al. (1999 b ) similarly demonstrated its genetic isolation relative to L. trimucronatus and L. sibiricus based on mitochondrial DNA analyses. Their study highlights the biogeographic importance of the Lena-Kolyma catchment, with L. trimucronatus ranging east of the Kolyma River, L. sibiricus ranging to the west of the Lena River, and L. amurensis found in-between; discontinuities in mitochondrial DNA sequences among samples of Dicrostonyx are also localized in the region of the Kolyma and Lena Rivers (Federov, 1999; Federov et al., 1999 a ). Includes chrysogaster , a form sometimes viewed as a species (e.g., Gileva et al., 1984; Gromov and Erbajeva, 1995). In identifying their Chukotskiy sample as the species chrysogaster , Gileva et al. (1984) inadvertently confused understanding of the taxonomy and ranges of these lemmings (see remarks under ...